The United Nations World Water Development Report 2019 - United Nations Educational, Scientific; Cultural Organization (United Nations, 2019)
The 2019 Report seeks to inform policy and decision-makers, inside and outside the water community, how improvements in water resources management and access to water supply and sanitation services are essential to overcoming poverty and addressing various other social and economic inequities. In an increasingly globalized world, the impacts of water-related decisions cross borders and affect everyone. Extreme events, environmental degradation, population growth, rapid urbanization, unsustainable and inequitable consumption patterns, conflicts and social unrest, and unprecedented migratory flows are among the interconnected pressures faced by humanity, often hitting those in vulnerable situations the hardest through their impacts on water. Addressing the inequalities faced by disadvantaged groups requires tailored solutions that take account of the day-to-day realities of people and communities in vulnerable situations. Properly designed and adequately implemented policies, efficient and appropriate use of financial resources, as well as evidence-based knowledge on water resources and water-related issues are also vital to eliminating inequalities in access to safe drinking water and sanitation. Titled ‘Leaving No One Behind ’, the report reinforces the commitments made by the UN member states in adopting the 2030 Agenda for Sustainable Development and in recognizing the human rights to safe drinking water and sanitation, both of which are essential for eradicating poverty and for building prosperous, peaceful societies.